An Occupational Risk Analysis in the Bituminous Emulsion Transport and Spreading Process: A Case Study Applied in a Company in Romania - Adriana Milea (Pârvu); Lucian-Ionel Cioca (Safety)
This paper analyzes the occupational risks associated with the activities of transporting and spreading bituminous emulsion, focusing on a specific technological process used in a company in Romania. This study aims to identify risk factors, systematically evaluate them, and propose preventive measures aimed at reducing occupational accidents and diseases. The main hazards identified include exposure to hazardous chemicals, mechanical risks generated by the equipment used, and ergonomic factors that may affect workers’ health. Given the specificity of the activity analyzed, there is currently a lack of relevant studies specifically addressing the occupational safety and health of this category of workers, which further highlights the novelty and importance of the present research. Based on the results obtained, recommendations are formulated for optimizing work conditions, including the use of appropriate protective equipment, improving operational procedures, and implementing effective technical and organizational measures. This study contributes to the development of a solid preventive framework in the field of transporting and applying bituminous emulsion, thus supporting the improvement of occupational safety and health in the road construction industry. The results obtained can be used to develop more effective policies in the field of occupational safety and to raise awareness among decision-makers about the need for proactive measures in preventing occupational risks.